Melatonin's Impact on Wound Healing - Sohn, Eun-Hwa; Kim, Su-Nam; Lee, Sung-Ryul (MDPI AG, 2024)
Melatonin (5-methoxy-N-acetyltryptamine) is an indoleamine compound that plays a critical role in the regulation of circadian rhythms. While melatonin is primarily synthesized from the amino acid tryptophan in the pineal gland of the brain, it can also be produced locally in various tissues, such as the skin and intestines. Melatonin's effects in target tissues can be mediated through receptor-dependent mechanisms. Additionally, melatonin exerts various actions via receptor-independent pathways. In biological systems, melatonin and its endogenous metabolites often produce similar effects. While injuries are common in daily life, promoting optimal wound healing is essential for patient well-being and healthcare outcomes. Beyond regulating circadian rhythms as a neuroendocrine hormone, melatonin may enhance wound healing through (1) potent antioxidant properties, (2) anti-inflammatory actions, (3) infection control, (4) regulation of vascular reactivity and angiogenesis, (5) analgesic (pain-relieving) effects, and (6) anti-pruritic (anti-itch) effects. This review aims to provide a comprehensive overview of scientific studies that demonstrate melatonin's potential roles in supporting effective wound healing.